Kitāb Bahasa Arab al-Madrasī Li aṣ-Ṣaff ar-Rābi` al-Ibtidā’ī Wa Taḥlīluhu Min Ḥaiṡ Tadarruj al-Mādah - Salvina Ulfa; Azwir Azwir (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2022)
In the teaching-learning process, there are several components interrelated with each other. These components include students, teachers, objectives, materials, methods, media, and evaluation. The criteria for the content of textbooks that are suitable for use by education units have been determined by the BNSP as stated in the Regulation of the Education Minister and Culture of the Republic of Indonesia No. 8 of 2016 concerning books used in educational units article 3 paragraph 5 that the content of the textbook of lesson must cover aspects of material, linguistic, material presentation, and graphic. Besides these four aspects, teaching materials also need to be considered in a textbook. Teaching materials in textbooks are not only in accordance with the curriculum, but also they must be of high quality. William Francis Mackey explained the aspects of seeing the quality of language teaching materials in a textbook, namely the aspects of selecting, gradation, presentation, and repetition. The researcher found that the subject matter for the fourth grade of the elementary school was not in the order and the grammar presented in the fourth grade of the elementary school was more than the grammar presented in the fifth Arabic for the elementary school. Therefore, the researcher analyzed the "fourth-grade Arabic textbook at the Elementary School" to find out the contents of the book, according to the level of material gradation, and also to determine the suitability of the book content with the principles of good book presentation. In this study, the researcher used a descriptive method with the type of Content Analysis. The data collection techniques were documentation and literature review. In short, the results showed that the textbook has fulfilled the criteria for a good presentation of a textbook in terms of psychological, cultural, educational, and language principles. However, when viewed in terms of material quality, this book is not in accordance with the level of material gradation.